Justice perceptions and reappraisal: A path to preserving employee resilience. Issue 2 (15th March 2023) - Holley, Erica; Thiel, Chase; Avey, James
ABSTRACT: Lower levels of organizational justice relative to one's peers can negatively influence an employee's well-being, diminish work satisfaction, and increase apathy. However, not all employees that perceive lower organizational justice respond in the same way. Using affective events theory as a theoretical framework, we draw on the organizational justice, resilience, and emotions literatures to identify a critical factor that may facilitate adaptive responses to lower organizational justice and preserve employee resilience. We propose that cognitive reappraisal, an antecedent-focused emotional regulation strategy, may attenuate the negative impact of lower organizational justice on employee resilience, and ultimately, protect other critical employee outcomes (i.e employee psychological well-being, job satisfaction, and citizenship behavior). Across two large field surveys of employees, we find support for our model.